Fatores relevantes no processo de transferência de tecnologia na implementação do sistema de planejamento e controle da produção na indústria Metalgráfica Iguaçu S.A. - Escorsim, Sergio (2006)
This research identifies the relevant factors in the technology transfer process when a new management technique is implemented. In the productive sector, the production planning presents itself as an essential instrument for guaranteeing the organizational efficiency. An effective planning is the differential of an organization that merely adequate itself from a really superior one. The major difficulty of the production managers is to identify which the factors that may influence in the technology transfer are. In order to achieve the objective of this work, it was carried out an exploratory research, of applied nature and qualitative approach. The case study was done in Metalgráfica Iguaçu S.A., a large metalmechanic industry in the region of Campos Gerais, centre south of Paraná, Brazil, which developed and implemented a module of Enterprise Resources Planning (ERP), the Production Planning and Control Software SPX. The results of this research show that the company was successful in the technology transfer. The most relevant factors were the competence of the specialist involved in the development of the system, the financial and logistic support from the high Administration and the interest and motivation of the intervenient. The primordial function of this study is to provide subsidies to industrial managements, helping them in the decision making process when implementing a new industrial management technique.